Alisol Triterpenoids Exhibit Triple Modulatory Mechanisms on the Cell Membrane to Overcome Cancer Multidrug Resistance - Chen JY; Chang YT; Ho YC; Teng YN (Drug Design, Development and Therapy)
Jing-Yi Chen,1,* Ying-Tzu Chang,2,* Yu-Cheng Ho,3 Yu-Ning Teng2– 4 1Department of Medical Laboratory Science, College of Medical Science and Technology, I-Shou University, Kaohsiung, Taiwan, Republic of China; 2Department of Pharmacy, College of Pharmacy, China Medical University, Taichung City, Taiwan, Republic of China; 3School of Medicine, College of Medicine, I-Shou University, Kaohsiung, Taiwan, Republic of China; 4Department of Pharmacy, E-Da Cancer Hospital, Kaohsiung, Taiwan, Republic of China*These authors contributed equally to this workCorrespondence: Yu-Ning Teng, Department of Pharmacy, College of Pharmacy, China Medical University, 100, Sec. 1, Jingmao Road, Beitun Dist, Taichung City, 406040, Taiwan, Republic of China, Tel +886-4-22053366 ext. 5158, Fax +886-4-22078083, Email ynteng@mail.cmu.edu.tw; eunicegh520@gmail.comPurpose and Study Design: Multi-drug resistance (MDR) in cancer significantly hinders effective treatment, leading to poor patient outcomes. The study investigates the potential of natural compounds, Alisol B 23-acetate (B23) and Alisol A 24-acetate (A24), to reverse MDR through various mechanisms on cancer cell membranes.Results: Cytotoxicity assays established non-toxic concentrations of B23 and A24, which were then tested in drug-sensitive and drug-resistant cancer cell lines with or without chemotherapeutic drugs. Both compounds significantly enhanced reactive oxygen species (ROS) production and apoptosis in HepG2/VIN MDR cells while preserving cell membrane integrity. They also improved membrane fluidity and inhibited the function of P-glycoprotein (P-gp) efflux transporters in both HepG2/VIN and ABCB1/Flp-InTM-293, leading to increased drug accumulation. Molecular docking studies revealed that B23 and A24 interact with distinct binding sites on P-gp, demonstrating allosteric and competitive inhibition.Conclusion: B23 and A24 effectively reverse cancer MDR by (1) modulating ROS levels and inducing apoptosis, (2) maintaining membrane integrity but improving membrane fluidity, and (3) inhibiting drug efflux by membrane transporters. These findings provide a promising basis for developing new therapeutic strategies to combat MDR in cancer, highlighting the potential use of these natural product derivatives in adjunctive cancer therapy. Keywords: alisol triterpenoids, multi-drug resistance, cell membrane fluidity, efflux transporter inhibitor, reactive oxygen species